Організаційно-економічні проблеми фінансування інноваційної діяльності в Україні - Пилип’юк, Я.В. (Культура народов Причерноморья, 2013)
У статті розглянуто сучасний стан економіки України у питанні переходу на інноваційний
шлях розвитку та проблеми, які виникають в процесі цієї діяльності. Здійснено аналіз загального стану
фінансового забезпечення інноваційної діяльності в Україні та основних джерел фінансування інновацій.
Охарактеризовано загальну тенденцію фінансування інноваційної діяльності в Україні за 2000-2011
роки. Виявлено основні проблеми фінансування інноваційної діяльності в Україні.
Зазначено заходи підвищення зацікавленості інвесторів у фінансуванні інноваційних проектів. Вказано
додаткові стимули фінансуванні інноваційної діяльності та визначено окремі напрями покращення
фінансового забезпечення інноваційної діяльності.
Ключові слова: інновації, інноваційний розвиток, джерела фінансування, фінансове забезпечення
інноваційної діяльності. В статье рассмотрено современное состояние экономики Украины в вопросе перехода на
инновационный путь развития и проблемы, которые возникают в процессе этой деятельности.
Осуществлен анализ общего состояния финансового обеспечения инновационной деятельности в
Украине и основных источников финансирования инноваций. Охарактеризованы общую тенденцию
финансирования инновационной деятельности в Украине за 2000-2011 годы. Выявлены основные
проблемы финансирования инновационной деятельности в Украине.
Отмечено меры повышения заинтересованности инвесторов в финансировании инновационных
проектов. Указана дополнительные стимулы финансировании инновационной деятельности и
определены отдельные направления улучшения финансового обеспечения инновационной деятельности.
Ключевые слова: инновации, инновационное развитие, источники финансирования, финансовое
обеспечение инновационной деятельности. The article reviews present economic situation in Ukraine in the transition to an innovative way of
development and the problems that occur during this activity. The overall financial support of innovative
activity in Ukraine and major sources of funding innovation are analyzed. The general trend of financing of
innovation in Ukraine for the years 2000-2011 is characterized.
Main problems of financing innovation are detected. Among them it is emphasised on such problems as lack of
financial resources for innovation and complexity of commercialization of results from scientific and
technological activities.
Measures to improve investors’ interest in funding innovative projects are indicated. Additional incentives of
financing innovation are specified and some directions of improvement of financial support of innovation are
identified.
The development of science and its funding plays particularly important role in the activation of innovative
activity in our country. It is examined that without a developed market of innovation normal functioning of a
modern market economy is impossible.
It is established that the policy of stimulation research and innovative activity can provide the dynamic
development of the economy. It will be the foundation for improving living standards.
It was concluded that to enhance innovative activity of ukrainian companies the issue of promoting financial
support in this field at the national level must be solved.
Using innovations significantly affects the acceleration of restructuring the economy and increases its
investment attractiveness, competitiveness and financial stability. That is why in modern terms it is very
important to create favorable conditions for the development of innovative processes.
Keywords: innovation, innovative development, funding, financial support of innovation.